2016
DOI: 10.2323/jgam.62.7
|View full text |Cite
|
Sign up to set email alerts
|

Cultivation of freshwater microalga <i>Scenedesmus</i> sp. using a low-cost inorganic fertilizer for enhanced biomass and lipid yield

Abstract: of 28.55 and 18.87, respectively, in a stationary phase of the microalgae growth. The fatty acids methyl ester profile was proven to be desirable for biodiesel production.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
9
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 32 publications
1
9
0
2
Order By: Relevance
“…Despite of the several benefits from this microalga, its commercial scale production is still not cost-effective if algae are required in large amount (Di Caprio et al 2015;Nayak et al 2016b). Xia and Murphy (2016) reported that in large-scale production, nutrient requirements can be up to 50% of the total cost of biomass production.…”
Section: Introductionmentioning
confidence: 99%
“…Despite of the several benefits from this microalga, its commercial scale production is still not cost-effective if algae are required in large amount (Di Caprio et al 2015;Nayak et al 2016b). Xia and Murphy (2016) reported that in large-scale production, nutrient requirements can be up to 50% of the total cost of biomass production.…”
Section: Introductionmentioning
confidence: 99%
“…The use of organic fertilizers such as animal excreta, sludge from wastewater, and anaerobic digestate with high nutrient contents has been proposed as an economical alternative for microalgae culture (Nayak et al 2016, Wang et al 2016a, El Shimi and Moustafa 2017, Liu et al 2017, Huy et al 2018. The use of wastewater (Gonçalves et al 2017, Ho et al 2019, Rodríguez-Mata et al 2019) and wastewater enriched with inorganic fertilizers, composed of N, P, and potassium (K), is an economical alternative for large-scale cultivation (Nayak et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Se ha propuesto la utilización de fertilizantes orgánicos como excretas animales, lodos de aguas residuales y digestatos anaerobios con alto contenido de nutrientes como una alternativa económica para el cultivo de microalgas (Nayak et al 2016, Wang et al 2016a, El Shimi y Moustafa 2017, Liu et al 2017, Huy et al 2018. La utilización de aguas residuales (Gonçalves et al 2017, Ho et al 2019, Rodríguez-Mata et al 2019) y aguas residuales enriquecidas con fertilizantes inorgánicos, compuestos por N, P y potasio (K), es una alternativa económica para el cultivo a gran escala (Nayak et al 2016).…”
Section: Introductionunclassified
“…The medium has been used to grow Scenedesmus sp. and able to produce high lipids of 28.55% of the total biomass 25) . Comparison of NPK commercial fertilizers used, which is equal to 20:20:20.…”
Section: Introductionmentioning
confidence: 99%